Access Control for Autborized Video in Information-Centric Networking - Zifei Zhou; Xiaobin Tan; Yukun Niu; CZou Cliff (Dianxin kexue)
Information-centric networking（ICN）can greatly improve the efficiency of video content, however, in-network caching in ICN also brings us a new access control challenge. The purpose of authorized video access control is to ensure that only authorized users can watch them, and to prevent unauthorized accesses to these authorized videos. In ICN, when authorized videos were cached in the routers, anyone can get and watch them without the authorized videos' producers' permission. The existing methods could not solve this problem well, an access control scheme was proposed that based on splitting and digital watermarking. The authorized video was splitted into two parts, public content block（PCB）and content key block（CKB）, respectively. PCB which was generally relatively large, was the same for all users, and CKB which was generally relatively small, was unique for each authorized users using digital watermarking technology. Users must received both PCB and CKB to watch videos. After the analysis, the access control scheme for authorized videos has a good performance in both security and network resource optimization.